1976
DOI: 10.1002/j.1879-3479.1976.tb00626.x
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma in situ of the Fallopian Tube Associated with Cervical Carcinoma: Case Report

Abstract: A case of carcinoma in situ of the fallopian tube in a 55-year-old woman, associated to cervical carcinoma is described. The necessary criteria for the diagnosis of pre-invasive carcinoma of the fallopian tube, among which the number of mitoses seems to be of great importance, are discussed. This previously unreported association of carcinoma in situ of the fallopian tube, with carcinoma of the uterine cervix, emphasizes the notion of the multicentric neoplastic possibilities of the müllerian tract derivatives. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

1979
1979
1998
1998

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…Primary carcinoma of the fallopian tube is mostly papillary adenocarcinoma of serous type, seen in our case. So far, only a few cases of carcinoma in situ of the fallopian tube have been reported, 6 but its detailed clinical and pathologic findings, including cytology, have not been described except for one recent report. 7 Unlike the case from Luzzatto et al, 7 psammoma bodies were not found in our case.…”
Section: Discussionmentioning
confidence: 99%
“…Primary carcinoma of the fallopian tube is mostly papillary adenocarcinoma of serous type, seen in our case. So far, only a few cases of carcinoma in situ of the fallopian tube have been reported, 6 but its detailed clinical and pathologic findings, including cytology, have not been described except for one recent report. 7 Unlike the case from Luzzatto et al, 7 psammoma bodies were not found in our case.…”
Section: Discussionmentioning
confidence: 99%
“…(2), (6), ' • (28). El segundo caso lo describe 'Hokitanski en 1861 (2), (6), (28), y el primer caso publicado en la literatura médica lo realizó Orthman en 1888 (2), (6), (11), de un caso el ínico intervenldo por Martín en 1866, (2) 1965 reunidos por Jones y 829 en 1967 \2), a los que se suman 26 casos informados por Kinzel en 1975 (16), 20 casos de Wolf en 1976 (33), 31 casos de Kubista en 1977 (17), 24 casos de Barth en 1980 (4), 22 casos de Raju en 1981 (24), 15 casos de Tamimi en 1981 (19), 37 casos de Engeler en 1981 (8), y los últimos 16 casos informados en la literatura mundial por Herhey, recopilados en 8 hospitales del estado de Colorado (USA) y publicados en marzo de 1981 con los cuales se completan un total de 1100 casos, desde el primero publicado por Orthman en 1888 (11). (Tabla No.…”
unclassified